Experimental climate warming alters the relationship between fungal root symbiosis and Sphagnum litter phenolics in two peatland microhabitats. (February 2017) - Binet, Philippe; Rouifed, Soraya; Jassey, Vincent E.J.; Toussaint, Marie-Laure; Chiapusio, Geneviève
Abstract: Belowground interactions between plants and microorganisms are involved in numerous ecosystems processes such as carbon and nutrient cycling. Understanding their responses to on-going climate warming is thus of paramount importance to better predict future ecosystem functioning. We hypothesized that climate warming alters the interactions between Sphagnum litter phenolics and the fungal root symbiosis of the Ericale plant Andromeda polifolia in a Jura mountain peatland (France). We initiate a climate warming treatment (+1 °C) in April 2008 in two microhabitats (lawns and hummocks). We measured polyphenolic contents, mycorrhizal and dark septate endophyte (DSE) root colonization, phenoloxidase and peroxidase activities in the A. polifolia rhizosphere from 2010 to 2012. We found that four years of warming modulated rhizospheric parameters (fungal root symbiosis and enzyme activities) of A. polifolia, but the response differed between microhabitats. Enzyme activities and fungal root colonization displayed different responses to warming according to the microhabitats. DSE root colonization increased and peroxidase activities decreased in warmed Hummocks while they remained stable in warmed lawns. We found a significant positive correlation between DSE root colonization and litter phenolics recovered in both microhabitats but only under in ambient conditions. On the contrary, significant negative correlation was observed between mycorrhizae and litter phenolics recovered in warmed plots while no relationship was found in control plots. Our work thus provides evidences that interplay between phenolics from Sphagnum litter and fungal symbiosis of an Ericale species in peatlands was affected by climate warming. It highlights different plant biological responses to climate warming according to peatland microhabitats and confirm that belowground activities are crucial to understand the response of peatlands to climate change. Highlights: Sphagnum phenolic production stimulated Andromeda fungal root colonization. This positive relationship changed to negative under an experimental climate warming. Warming increased fungal root colonization and decreased peroxidase activities. Warming influenced rhizospheric parameters according to peatland microhabitats.